BASED ON TALENT MANAGEMENT AS EMPLOYEE PERFORMANCE OPTIMIZATION BY STRENGTHENING EMPLOYEE RETENTION ASPECT - Hermawati, Adya; Rizka, Afinna Septa; Bahri, Syamsul; Djawoto, Djawoto; Hendarto, Totok (Jurnal Aplikasi Manajemen, 2021)
This study aims to obtain empirical evidence that good Talent Management will improve employee performance to be optimal, consistent employee retention, consistent employee retention will increase optimal employee performance, and consistent employee retention will increase optimal employee performance at PT. Panahmas Ekatama Distrindo Malang. The research approach is explanatory research. Data were collected with a survey method that uses questionnaires. The population of the research was counted as 96 person result of the research showed that (1) good talent management will produce optimum employee performance; (2) good talent management will deliver consistent employee retention; (3) consistent employee retention will engender optimum. Employee performance; and (4) good talent management can produce employee performance through consistent employee retention. Theoretically, the usefulness of this research is to contribute to the fields of Human Resource Management, Talent Management, Employee Retention, and Employee Performance.